1973
DOI: 10.1111/j.1365-3083.1973.tb02031.x
|View full text |Cite
|
Sign up to set email alerts
|

Receptors for Immunoglobulin Fc in Human Malignant Tissues

Abstract: Cryostat sections of 10 malignant human tumours of various types strongly adsorbed erythrocytes sensitized with IgG antibodies Normal spleen and lymph nodes showed medium Strong and thymus weak reactions. The receptors in tissue have affinity for the Fc‐portion of Ig, and (phospho)lipids are common consituents. An antiserum to a lymphoma inhibited receptor activity of all tissues. Spleen and tumour tissue removed this inhibiting activity. Tentatively, the malignant tissue seems to carry membrane receptor(s) si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
17
1

Year Published

1974
1974
1985
1985

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 81 publications
(23 citation statements)
references
References 16 publications
5
17
1
Order By: Relevance
“…Our observation of tumor cell binding of fluorescent IgG aggregates confirmed previous reports by T0nder and Thunold (26). It …”
Section: Introductionsupporting
confidence: 92%
“…Our observation of tumor cell binding of fluorescent IgG aggregates confirmed previous reports by T0nder and Thunold (26). It …”
Section: Introductionsupporting
confidence: 92%
“…Recent experimental results of T o n d er and T h u n o l d [84] support this contention that at least B lymphocytes and malignant cells share a common antigen. The shared antigen fixes IgG Fc [84], and this could represent Fc binding to a previously cell-bound (esteroproteolytic) C' component.…”
Section: The Detendomer and Malignant Changesupporting
confidence: 56%
“…Although Wood & Gollahon (1977) demonstrated Fc(IgG) receptor-bearing cells in breast tumours, some investigators believe that malignant cells can express such receptors (Tonder & Thunold, 1973;Svennevig & Andersson, 1982). Morphologically, macrophages are not readily delineated in tissue sections of carcinomas, and in tumour cell suspensions precise identification is likewise difficult.…”
mentioning
confidence: 99%
“…Although the Fc(IgG) receptor has been widely used as a macrophage marker in tumour cell suspensions (Russell et al, 1981), some workers have suggested that malignant cells themselves may express Fc(IgG) receptors (Tonder & Thunold, 1973;Svennevig & Andersson, 1982). In addition, it has been shown that human monocytes can shed these receptors in culture (Kay & Douglas, 1981), raising the possibility of nonspecific receptor uptake by tumour cells.…”
mentioning
confidence: 99%